The clinical strategies for tendon repair with biomaterials: A review on rotator cuff and Achilles tendons. Issue 5 (30th November 2019) - Veronesi, Francesca; Borsari, Veronica; Contartese, Deyanira; Xian, Jie; Baldini, Nicola; Fini, Milena
Abstract: Tendon repair is a complex process due to the low tenocyte density, metabolism, and vascularization. Tears of rotator cuff (RCT) and Achilles tendons ruptures have a major impact on healthcare costs and quality of life of patients. Scaffolds are used to improve the healing rate after surgery and long‐term results. A systematic search was carried out to identify the different types of scaffolds used during RCT and Achilles tendon repair surgery in the last 10 years. A higher number of clinical studies were reported on RCT ruptures. Biological scaffolds were used more than synthetic ones, for both rotator cuff and Achilles tendons. Moreover, platelet‐rich plasma (PRP)‐based scaffolds were the most widely used in RCT. A different type of synthetic scaffold was used in each of the five studies found. Biological scaffolds either provide variable results, in particular PRP‐based ones, or poor results, such as bovine equine pericardium. All the synthetic scaffolds demonstrated a significant increase in clinical and functional scores in biomechanics, and a significant decrease in pain and re‐tear rate in comparison to conventional surgery. Despite the limited number of studies, further investigation in the clinical use of synthetic scaffolds should be carried out.